Electroconvulsive shock and transcranial magnetic stimulation do not alter the survival or spine density of adult-born striatal neurons. - Tara Gaertner; Tian Rui Zhang; Baran Askari; Fidel Vila-Rodriguez; Jason S Snyder (PLoS ONE)
Adult neurogenesis has most often been studied in the hippocampus and subventricular zone-olfactory bulb, where newborn neurons contribute to a variety of behaviors. A handful of studies have also investigated adult neurogenesis in other brain regions, but relatively little is known about the properties of neurons added to non-canonical areas. One such region is the striatum. Adult-born striatal neurons have been described in both rodents and humans, but the regulation of these neurons is poorly understood. Since striatal dysfunction occurs in Parkinson's disease, which is amenable to neurostimulation therapies, we investigated whether electroconvulsive shock (ECS) or transcranial magnetic stimulation (rTMS) modulate neuroplasticity of adult-born striatal neurons. Adult-born cells were labelled in transgenic mice and 8 days later mice were given 10 stimulations over the course of 3 weeks. Adult-born striatal neurons were consistently observed in all groups. Their dendritic morphology and expression of DARPP32 and NeuN indicated a medium spiny neuron phenotype. However, neither ECS nor rTMS altered the number of new neurons, and both treatments also had no effect on the density of dendritic spines compared to unstimulated controls. These results suggest that neither ECS nor rTMS alter early neuronal survival or morphological plasticity at postsynaptic sites in the striatum.